Residential Distribution System Harmonic Mitigation Using PV Interfacing Inverter - B. Mouli Chandra, T. Kishore Kumar, T. Pavan Kumar, N. Narasimha Rao (Mathematical Statistician and Engineering Applications, 2023)
In this study, electricity quality was improved in residential areas by adopting distributed generating systems. In the distribution network, active and passive filters are utilised to counteract a harmonic resonance in residential areas. The harmonics were corrected to enhance distribution generation (DG) using a photovoltaic interface inverter. For utility providers, the rising non-linear demands in the typical home of today constitute a significant worry. The harmonic resonance generated by the installation of capacitor banks in the distribution network might make the issue worse. Passive or active filters are frequently employed to reduce harmonic distortions. Harmonic distortions caused by an increase in the use of electronic gadgets in households are a significant problem for utility providers. In addition to the deteriorating power quality, the harmonic current flow may disrupt the nearby phone lines. Because home loads are distributed, it is challenging to measure harmonics in a residential system. The possibility of employing photovoltaic (PV) interface inverters to correct the harmonics in home systems is investigated in this study. First, a system model including the residential load and DG is created. Then, using the virtual harmonic damping impedance idea, several compensation systems are thoroughly analysed and compared. Studies are also done on the system’s capacitor banks’ impacts. Through research and simulations, the efficiency of the harmonic compensatory schemes is confirmed under various scenarios.